Meningkatkan Hasil Belajar dalam Pembelajaran Pendidikan Agama Katolik dan Budi Pekerti Materi Pribadi yang Unik Melalui Problem Based Learning di Kelas X Fase E SMA Negeri 1 Pajangan Kabupaten Bantul - Yustinus Tyasmanto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve students' learning outcomes on the topic of "Unique Personality" in Catholic Religion and Moral Education at Class X Phase E in SMA Negeri 1 Pajangan using Problem-Based Learning (PBL). The research subjects were six students who struggled with this material. Conducted in two cycles, the study followed four stages: planning, action, observation, and reflection. Results show a significant improvement in students' learning outcomes, with an average score increase from Cycle I to Cycle II. The PBL method positively impacted students' understanding and active participation. The study suggests applying PBL in other subjects to enhance learning outcomes.